Meningkatkan Kualitas Literasi Masyarakat Kelurahan Air Tawar Barat dengan Penerapan E-Library - Oktami, Ikhsan; Pangesti, Nesa Riska (Universitas Negeri Padang, 2023)
This paper aims to facilitate and improve public literacy, especially school age and equivalent. It is necessary to carry out evaluation actions in the school environment for literacy, especially reading interest. This is proven from the results of UNESCO's research (2016) on Indonesia which shows that only 1 person has an interest in reading as well as a report from PISA (Program Of International Student Assessment) 2018 Indonesia is ranked in the bottom 6 of 78 countries in terms of reading. The younger generation, especially students, must be instilled or instilled a critical literacy attitude to obtain truth information, knowledge, enlightenment and avoid false information (HOAX) and theories that have no knowledge base. Libraries have a vital role in terms of providing information and reference sources of knowledge. Therefore, the authors want to implement E-Library in the library as an effort to facilitate the public in obtaining information and increasing students' reading interest by using artificial intelligence that helps students understand the material or information provided efficiently and easily. The application of e-library has changed the perspective of Generation Alpha and Generation Z of libraries and the selection of libraries as sources of information and references. The results of this study change the point of view of users from generation Alpha and generation Z to the library as a printed or digital reference source in meeting information needs.